Preparation method of Ni-Co-Fe doped electrode for rapid uranium removal

By depositing Co and Fe elements on the foam nickel substrate to form Ni-Co-Fe doped electrodes, the problem of low uranium extraction and recovery efficiency in the prior art is solved, and rapid and efficient removal of uranium and improved stability of electrodes are achieved.

CN120247184AActive Publication Date: 2025-07-04SHANDONG UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510462852.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-14
Publication Date
2025-07-04
Estimated Expiration
2045-04-14

AI Technical Summary

Technical Problem

The prior art faces the problems of low uranium concentration, long adsorption time, and competitive cation and hydrogen evolution reactions affecting adsorption amount and stability during the uranium extraction and recovery process, and it is difficult to achieve rapid and efficient removal of uranium.

Method used

A three-electrode system is adopted, with nickel foam as the substrate. After anodizing, Co and Fe elements are deposited on its surface in turn to form a Ni-Co-Fe doped electrode. The potential gradient between metals and the Mott-Schottky effect are used to accelerate the charge transfer at the interface, and the electrode configuration is optimized to improve the adsorption and removal efficiency of uranium.

Benefits of technology

It achieves rapid removal of uranium under low uranium concentration conditions, and achieves 100% removal efficiency within 30 minutes, significantly improving the adsorption amount of uranium and the stability of the electrode, and avoiding the occurrence of hydrogen evolution reaction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120247184A_ABST
    Figure CN120247184A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a Ni-Co-Fe doped electrode for rapidly removing uranium, and belongs to the technical field of electrochemical functional materials. The preparation method of the Ni-Co-Fe doped electrode for rapid uranium removal comprises the following steps: by using a three-electrode system and taking foamed nickel as a working electrode, firstly carrying out anodic oxidation on the working electrode, then carrying out cobalt deposition in an electrolyte containing a cobalt source, and finally carrying out iron deposition in an electrolyte containing an iron source, thereby obtaining the Ni-Co-Fe doped electrode. Foamed nickel is used as a substrate, Co elements are firstly deposited through an electro-deposition process, then Fe elements are further deposited, a Ni-Co-Fe electrode is formed, and metal gradient distribution is achieved. A built-in electric field is formed by the remarkable potential difference among the three metals, interface charge transfer is accelerated through the Mott-Schottky effect, the catalytic activity and stability of the electrode are further improved, and the uranium removal effect is remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of electrochemically functional materials, and more specifically relates to a preparation method of a Ni-Co-Fe doped electrode for rapid uranium removal. Background Art

[0002] Nuclear energy has the advantages of low carbon emissions and high efficiency, and is an irreplaceable energy supply. Uranium is the key raw material for nuclear fission and the main "fuel" for nuclear power. Natural uranium is the material basis for the development of the nuclear industry and is an important strategic resource and energy mineral. The reserves of uranium in seawater are abundant, and the effective utilization of it is of great significance for the development of nuclear energy. At the same time, as an element with radioactive toxicity and chemical toxicity, uranium entering natural water bodies may cause uranium pollution in groundwater or surface water, thus bringing potential ecological and human health risks. Therefore, the sustainable extraction and recovery of uranium resources is of great strategic significance for ensuring the green and sustainable development of nuclear energy and environmental safety.

[0003] Currently, the technologies applied to the extraction and recovery of uranium mainly include chemical precipitation method, extraction method, adsorption method, etc. The adsorption method is widely used because of its advantages such as simple operation and low cost. However, the traditional physical and chemical adsorption method faces the challenges of low uranium concentration in seawater and long adsorption equilibrium time. External electric field adsorption shows great potential due to its advantages such as large adsorption capacity and fast adsorption rate. However, under the drive of the electric field, coexisting competitive cations such as Na + 、K + 、Ca 2+ and Mg 2+ will occupy some active sites, and the inevitable competitive hydrogen evolution reaction under high voltage will also significantly reduce the uranium adsorption capacity and stability.

[0004] Therefore, it is of great significance to develop an external electric field adsorption method that can achieve rapid uranium adsorption and removal and has high adsorption capacity and stability. Summary of the Invention

[0005] The purpose of the present invention is to provide a preparation method of a Ni-Co-Fe doped electrode for rapid uranium removal to solve the problems existing in the above-mentioned prior art and achieve a significant improvement in the efficiency of electrocatalytic uranium extraction.

[0006] To achieve the above purpose, the present invention provides the following scheme:

[0007] One of the technical solutions of the present invention: provides a preparation method of a Ni-Co-Fe doped electrode for rapid uranium removal, including the following steps:

[0008] Using a three - electrode system, with nickel foam as the working electrode, first anodize it, then carry out cobalt deposition in an electrolyte containing a cobalt source, and finally carry out iron deposition in an electrolyte containing an iron source to obtain the Ni - Co - Fe doped electrode.

[0009] In the present invention, nickel foam is used as the substrate. The high specific surface area of nickel foam can provide sufficient loading space for the loaded metal, and its hierarchical pore structure can promote electrolyte penetration and bubble release, reducing the mass transfer resistance. After the anodization treatment in the present invention, a NiO / Ni(OH)₂ transition layer is formed on the surface, significantly enhancing the bonding strength between the substrate and the loaded metal. First, the present invention deposits Co element on the surface of the oxidized nickel foam through an electrodeposition process to form a Ni - Co electrode, and then further deposits Fe element on this basis to form a Ni - Co - Fe electrode, realizing the metal potential gradient distribution. The significant potential difference of 0.19 V between the three metals forms a built - in electric field, which accelerates the interfacial charge transfer through the Mott - Schottky effect.

[0010] The present invention prepares the Ni - Co - Fe doped electrode by the strategy of first depositing Co element and then depositing Fe element. Depositing Co element first and then Fe element can ensure the electrode potential gradient distribution, form an intermediate layer with higher conductivity, and provide a potential buffer platform for subsequent Fe deposition. The order of the two cannot be reversed. Reversing the order will destroy the electron synergy effect at the Co / Fe hetero - interface and cause the potential gradient distribution to be disordered.

[0011] Preferably, the reagent used for anodization is potassium hydroxide or potassium hydroxide; the concentration of the reagent used for anodization is 2 - 4 M; the voltage of anodization is 2 - 3 V, and the time is 20 - 30 min.

[0012] By controlling the type and concentration of the reagent used for anodization, as well as the voltage and time of anodization, the present invention can increase the active sites for the bonding between the surface and the metal, and at the same time enhance the bonding strength between the nickel foam substrate and the loaded metal. Beyond this range, there will be drawbacks such as the collapse of the porous structure of nickel foam and grain boundary corrosion.

[0013] Preferably, when carrying out cobalt deposition, the electrolyte consists of boric acid, ammonium chloride and a cobalt source; in the electrolyte for cobalt deposition, the concentration of boric acid is 0.5 - 1 M. Boric acid can improve the uniformity, compactness and functionality of the coating through multiple mechanisms such as buffering pH, complexing metal ions and inhibiting side reactions during electrodeposition; the concentration of ammonium chloride is 1 - 3 M, which can improve the conductivity during electrodeposition and, in cooperation with boric acid, form a smoother and brighter coating; the concentration of the cobalt source is 0.1 - 0.5 M; the cobalt source includes one or more of cobalt nitrate, cobalt sulfate and cobalt chloride.

[0014] Preferably, the current density of cobalt deposition is 20 - 40 mA / cm 2 , and the time is 15 - 20 min.

[0015] Preferably, during iron deposition, the electrolyte consists of boric acid, ammonium chloride, and an iron source; in the electrolyte during iron deposition, the concentration of boric acid is 0.5 - 1 M. Boric acid can improve the uniformity, denseness, and functionality of the coating through multiple mechanisms such as buffering pH, complexing metal ions, and inhibiting side reactions during electrodeposition; the concentration of ammonium chloride is 1 - 3 M, which can improve the conductivity during electrodeposition and, in cooperation with boric acid, form a smoother and brighter coating; the concentration of the iron source is 0.1 - 0.5 M; the iron source includes ferrous chloride and / or ferrous sulfate.

[0016] Preferably, the current density of iron deposition is 20 - 40 mA / cm 2 , and the time is 15 - 20 min.

[0017] By controlling the types and concentrations of reagents used during the deposition of cobalt and iron elements, as well as the current density and time during deposition, the present invention can achieve the synergistic optimization of the density of metal active sites, the interfacial electron coupling effect, and the structural stability. Beyond this range, drawbacks such as a decrease in electrode conductivity and dendrite growth will occur.

[0018] Preferably, before anodization, it further includes the step of cleaning the working electrode.

[0019] Further, the reagent used for cleaning includes hydrochloric acid, and the concentration of the hydrochloric acid is 0.05 - 0.1 M; the cleaning time is 20 - 40 min.

[0020] Further, the counter electrode of the three - electrode system includes a platinum electrode, the lateral cross - sectional size of the counter electrode is 1 - 4 cm × 1 - 4 cm, and the reference electrode includes an Ag / AgCl electrode.

[0021] The second technical solution of the present invention: provides a Ni - Co - Fe doped electrode prepared by the above - mentioned preparation method.

[0022] The third technical solution of the present invention: provides the application of the above - mentioned Ni - Co - Fe doped electrode in the field of uranium removal.

[0023] Further, when the Ni - Co - Fe doped electrode is applied in the field of uranium removal, the Ni - Co - Fe doped electrode is used as the cathode, graphite is used as the counter electrode, an Ag / AgCl electrode is used as the reference electrode, the voltage is - 0.1 V, and the time is 0 - 70 min.

[0024] The Ni-Co-Fe doped electrode of the present invention can achieve 100% uranium removal within 30 minutes under the condition that the initial uranium concentration is 50 mg / L.

[0025] The present invention discloses the following technical effects:

[0026] 1. The present invention uses a three-dimensional porous nickel foam substrate, which is significantly superior to traditional carbon cloth or flat electrode substrates, provides sufficient loading space for the loading of metal active substances, and has a high specific surface area and a hierarchical pore structure. A transition layer is formed on the surface of the nickel foam by anodic oxidation pretreatment, which improves the bonding strength between the substrate and the metal active layer and avoids the problem of active layer peeling that is prone to occur in the traditional direct deposition process.

[0027] 2. The present invention first adopts a stepwise electrodeposition strategy, first depositing Co element to form a Ni-Co core layer, and then depositing Fe element on the Ni-Co core layer to form an Fe shell layer, forming a Ni-Co-Fe doped electrode with a gradient metal distribution. Compared with the traditional one-step co-deposition process, the uniformity of metal distribution is improved, and at the same time, a Mott-Schottky heterojunction is formed by using the significant potential difference (ΔE = 0.19 V) between the three metals Ni, Co, and Fe, generating a built-in electric field to drive the rapid migration of interfacial electrons.

[0028] 3. Using the Ni-Co-Fe doped electrode of the present invention, 100% uranium can be removed within 30 minutes under the condition that the initial uranium concentration is 50 mg / L. Compared with the prior art, the uranium removal efficiency has been significantly improved. Description of the Drawings

[0029] Figure 1 SEM image of the surface of the original nickel foam in Example 1;

[0030] Figure 2 SEM image of the surface of the anodized nickel foam in Example 1;

[0031] Figure 3 SEM image of the surface of the Ni-Co-Fe doped electrode obtained in Example 1;

[0032] Figure 4 Tafel curves of the Ni-Co doped electrode obtained in Example 1 and the Ni-Fe-Co doped electrode obtained in Example 1;

[0033] Figure 5 Adsorption and removal effects of uranium by the nickel foam electrode obtained in Example 1, the anodized nickel foam electrode obtained in Example 1, the Ni-Co doped electrode obtained in Example 1, and the Ni-Fe-Co doped electrode obtained in Example 1;

[0034] Figure 6The adsorption and removal effect of the Ni-Fe-Co doped electrode obtained in Example 1 on uranium in solutions containing uranium of different concentrations;

[0035] Figure 7 This is a surface morphology of the Ni-Fe-Co doped electrode obtained in Example 1 after the adsorption and removal effect test on uranium in a uranium-containing solution is completed;

[0036] Figure 8 This is an X-ray photoelectron spectrum of the Ni-Fe-Co doped electrode obtained in Example 1 after the adsorption and removal effect test on uranium in a uranium-containing solution was completed. DETAILED DESCRIPTION

[0037] The present invention provides a Ni-Co-Fe doped electrode for rapid uranium removal, a preparation method thereof and its application in the field of uranium removal. The key to the application in the field of uranium removal lies in the field of extracting and recovering uranium from water bodies.

[0038] Uranium mainly exists in water in the form of hexavalent uranium (U(VI)). Hexavalent uranium ions are easily converted from hydroxide ions (OH - ) 2- , forming uranyl ions (UO2 2+ ). UO2 2+ Under certain conditions, it can be reduced to tetravalent uranium (U(IV)), which is easy to precipitate. Electrocatalysis is a technology that induces redox reactions through electron transfer under the influence of an external electric field. It is a key process for renewable energy conversion and environmental remediation. Combining electrocatalysis with the redox process of uranium can achieve the regeneration of electrode active sites: free UO2 in water 2+ It migrates to the negative electrode surface through electrostatic attraction, where it obtains electrons and is reduced to relatively fixed U(IV) or electrically neutral uranium species. At the same time, electrocatalytic technology can achieve efficient uranium extraction at low voltage, thereby avoiding the occurrence of hydrogen evolution reaction.

[0039] Improving the efficiency of electrocatalytic reduction is a key factor in achieving the extraction of uranyl ions. The efficiency of the electrocatalytic reaction mainly depends on the surface structure of the electrocatalyst and the reaction environment near the surface of the electrocatalyst. At present, methods to improve the electrocatalytic efficiency include modifying the catalyst, applying external forces, and optimizing the electrode configuration. It is worth noting that, unlike catalysts, the reaction kinetics and overall performance in the electrocatalytic process can be directly affected by optimizing the electrode configuration. By introducing different metal hybrid atoms of Ni, Co, and Fe inside and at the interface of the electrode, an electrode potential difference can be formed, driving the electrons near the interface to move toward the electrode in a directional manner, thereby enriching at the electrode interface. Therefore, optimizing the electrode configuration is crucial to improving the efficiency of electrocatalytic uranium extraction.

[0040] However, there has been little research on optimizing the electrode configuration in the prior art. Moreover, the conventional optimization configurations mainly introduce single metal hybrid atoms or introduce multiple different metal hybrid atoms at one time inside and at the interface of the electrode, which still cannot significantly improve the electrocatalytic uranium extraction efficiency.

[0041] Based on the above problems, the present invention adopts a strategy different from the prior art to prepare a Ni-Co-Fe doped electrode with a special structure by using nickel foam as a substrate and introducing different metal hybrid atoms on its surface in a specific order. This not only improves the binding strength between the doped metal and the substrate and the distribution uniformity of the doped metal, but also utilizes the Mott-Schottky heterojunction formed by the electrode with this specific structure to generate a built-in electric field to drive the rapid migration of interfacial electrons, significantly improving the adsorption and removal efficiency of uranium.

[0042] Now, various exemplary embodiments of the present invention will be described in detail. This detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, characteristics, and implementation schemes of the present invention.

[0043] It should be understood that the terms used in the present invention are only for describing specific embodiments and are not used to limit the present invention. Additionally, for the numerical ranges in the present invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Any intermediate value within any stated value or stated range, as well as each smaller range between any other stated value or intermediate value within the stated range, is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded from the range.

[0044] Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those of ordinary skill in the art to which the present invention pertains. Although the present invention only describes preferred methods and materials, any methods and materials similar or equivalent to those described herein can also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials related to the documents. In case of conflict with any incorporated document, the content of this specification shall prevail.

[0045] Without departing from the scope or spirit of the present invention, various improvements and changes can be made to the specific embodiments of the present invention specification, which are obvious to those skilled in the art. Other embodiments obtained from the specification of the present invention are obvious to those skilled in the art. The specification and embodiments of the present invention are merely exemplary.

[0046] Regarding the terms "comprising", "including", "having", "containing", etc. used herein, they are all open-ended terms, meaning including but not limited to.

[0047] It should be noted that the aspects not described in detail in the present invention are all conventional operation means in the art and are not the focus of the present invention.

[0048] Unless otherwise specified, the raw materials used in the following examples and comparative examples of the present invention are all commercially available products, and the sources of the commercially available products do not affect the technical effects of the present invention.

[0049] Example 1

[0050] This example provides the preparation of the Ni-Co-Fe doped electrode, and the specific steps are as follows:

[0051] 1) Ultrasonically clean nickel foam (3 cm × 3 cm × 0.3 cm) in 0.1 M HCl for 20 min.

[0052] 2) Prepare the Ni-Co-Fe doped electrode using a traditional two-electrode system in a single-chamber cell. Use a platinum electrode (transverse cross-sectional size 2 cm × 2 cm) as the counter electrode, an Ag / AgCl electrode as the reference electrode, and the above-mentioned cleaned nickel foam as the working electrode substrate. Anodize the nickel foam in 3 M KOH at a voltage of 3 V for 30 min.

[0053] 3) Prepare an aqueous solution of 0.65 M H3BO3, 1.86 M NH4Cl, and 0.3 M Co(NO3)2 as the electrolyte, and electro-deposit the anodized nickel foam electrode for 15 min at a direct current of 30 mA / cm 2 to obtain a Ni-Co doped electrode.

[0054] 4) Prepare an aqueous solution of 0.65 M H3BO3, 1.86 M NH4Cl, and 0.3 M FeCl2 as the electrolyte, and electro-deposit the above-mentioned Ni-Co doped electrode for 15 min at a direct current of 30 mA / cm 2 to obtain a Ni-Co-Fe doped electrode.

[0055] Characterize the surfaces of the nickel foam (original nickel foam), anodized nickel foam, and the obtained Ni-Co-Fe doped electrode used in Example 1 by scanning electron microscopy.

[0056] Figure 1 is the scanning electron micrograph of the surface of the original nickel foam in Example 1; Figure 2 is the scanning electron micrograph of the surface of the anodized nickel foam described in Example 1; Figure 3 is the scanning electron micrograph of the surface of the Ni-Co-Fe doped electrode obtained in Example 1.

[0057] From Figure 1 and Figure 2It can be seen that the surface roughness of the nickel foam after anodic oxidation increases significantly, and the active sites for binding with the metal on the surface increase. At the same time, the binding strength between the nickel foam substrate and the loaded metal can be improved. In comparison Figure 3 it can be known that obvious element deposition appears on the surface of the obtained Ni-Co-Fe doped electrode, and the active surface area increases, which is mainly attributed to the deposited Co and Fe elements on the surface.

[0058] Comparative Example 1

[0059] The difference from Example 1 is that "nickel foam" is replaced with "carbon cloth" of the same size, and others are the same as Example 1.

[0060] Comparative Example 2

[0061] The difference from Example 1 is that "nickel foam" is replaced with "flat electrode substrate (gold material)" of the same size, and others are the same as Example 1.

[0062] Comparative Example 3

[0063] The difference from Example 1 is that Co element and Fe element are deposited on the nickel foam at one time, and others are the same as Example 1.

[0064] Specifically:

[0065] 1) Ultrasonically clean the nickel foam (3 cm × 3 cm × 0.3 cm) in 0.1 M HCl for 20 min.

[0066] 2) Prepare the Ni-Co-Fe doped electrode by using the traditional two-electrode system in a single-chamber cell. Use a platinum electrode (transverse cross-sectional size 2 cm × 2 cm) as the counter electrode, an Ag / AgCl electrode as the reference electrode, and the above-mentioned cleaned nickel foam as the working electrode substrate. First, anodize the nickel foam in 3 M KOH at a voltage of 3 V for 30 min.

[0067] 3) Prepare an aqueous solution of 0.65 M H3BO3, 1.86 M NH4Cl, 0.3 M Co(NO3)2 and 0.3 M FeCl2 as the electrolyte, and electro-deposit the anodized nickel foam electrode for 15 min at a direct current of 30 mA / cm 2 to obtain the Ni-Co-Fe doped electrode.

[0068] Comparative Example 4

[0069] The difference from Example 1 is that the deposition order of Co element and Fe element is swapped, and others are the same as Example 1.

[0070] Specifically:

[0071] 1) Ultrasonically clean the nickel foam (3 cm × 3 cm × 0.3 cm) in 0.1 M HCl for 20 min.

[0072] 2) The traditional two - electrode system in a single - chamber cell was used to prepare the Ni - Co - Fe doped electrode. A platinum electrode (with a transverse cross - sectional size of 2 cm×2 cm) was used as the counter electrode, an Ag / AgCl electrode was used as the reference electrode, and the above - cleaned nickel foam was used as the working electrode substrate. The nickel foam was first anodized at a voltage of 3 V in 3 M KOH for 30 min.

[0073] 3) An aqueous solution of 0.65 M H3BO3, 1.86 M NH4Cl, and 0.3 M FeCl2 was prepared as the electrolyte. The anodized nickel foam electrode was electrodeposited at a direct - current density of 30 mA / cm 2 for 15 min to obtain the Ni - Fe doped electrode.

[0074] 4) An aqueous solution of 0.65 M H3BO3, 1.86 M NH4Cl, and 0.3 M Co(NO3)2 was prepared as the electrolyte. The above - mentioned Ni - Fe doped electrode was electrodeposited at a direct - current density of 30 mA / cm 2 for 15 min to obtain the Ni - Fe - Co doped electrode.

[0075] Comparative Example 5

[0076] The difference from Example 1 is: adjusting the conditions of nickel foam anodization, and the others are the same as in Example 1.

[0077] Specifically:

[0078] 1) The nickel foam (3 cm×3 cm×0.3 cm) was ultrasonically cleaned in 0.1 M HCl for 20 min.

[0079] 2) The traditional two - electrode system in a single - chamber cell was used to prepare the Ni - Co - Fe doped electrode. A platinum electrode (with a transverse cross - sectional size of 2 cm×2 cm) was used as the counter electrode, an Ag / AgCl electrode was used as the reference electrode, and the above - cleaned nickel foam was used as the working electrode substrate. The nickel foam was first anodized at a voltage of 5 V in 1 M NaOH for 30 min.

[0080] 3) An aqueous solution of 0.65 M H3BO3, 1.86 M NH4Cl, and 0.3 M Co(NO3)2 was prepared as the electrolyte. The anodized nickel foam electrode was electrodeposited at a direct - current density of 30 mA / cm 2 for 15 min to obtain the Ni - Co doped electrode.

[0081] 4) An aqueous solution of 0.65 M H3BO3, 1.86 M NH4Cl, and 0.3 M FeCl2 was prepared as the electrolyte. The anodized nickel foam electrode was electrodeposited at a direct - current density of 30 mA / cm 2Under a direct current of [value] for 15 minutes, the above Ni-Co doped electrode was electro-deposited to obtain a Ni-Co-Fe doped electrode.

[0082] Comparative Example 6

[0083] The difference from Example 1 was: adjusting the electrode electro-deposition conditions, with other conditions the same as in Example 1.

[0084] Specifically:

[0085] 1) The nickel foam (3 cm × 3 cm × 0.3 cm) was ultrasonically cleaned in 0.1 M HCl for 20 minutes.

[0086] 2) A Ni-Co-Fe doped electrode was prepared using a traditional two-electrode system in a single-chamber cell. A platinum electrode (with a transverse cross-sectional size of 2 cm × 2 cm) was used as the counter electrode, an Ag / AgCl electrode was used as the reference electrode, and the above cleaned nickel foam was used as the working electrode substrate. The nickel foam was first anodized at a voltage of 3 V in 3 M KOH for 30 minutes.

[0087] 3) An aqueous solution of 0.65 M H3BO3, 1.86 M NH4Cl, and 0.3 M Co(CO3)2 was prepared as the electrolyte. Under a direct current of [value] for 15 minutes, the anodized nickel foam electrode was electro-deposited to obtain a Ni-Co doped electrode. 2 Under a direct current of [value] for 15 minutes, the anodized nickel foam electrode was electro-deposited to obtain a Ni-Co doped electrode.

[0088] 4) An aqueous solution of 0.65 M H3BO3, 1.86 M NH4Cl, and 0.3 M Fe2(SO4)3 was prepared as the electrolyte. Under a direct current of [value] for 15 minutes, the above Ni-Co doped electrode was electro-deposited to obtain a Ni-Co-Fe doped electrode. 2 Under a direct current of [value] for 15 minutes, the above Ni-Co doped electrode was electro-deposited to obtain a Ni-Co-Fe doped electrode.

[0089] Performance test:

[0090] 1. Catalytic activity and stability test of the electrode:

[0091] Using the Ni-Co doped electrode obtained in Example 1 and the Ni-Fe-Co doped electrode obtained in Example 1 as the working electrodes, a platinum electrode (with a transverse cross-sectional size of 2 cm × 2 cm) as the counter electrode, and an Ag / AgCl electrode as the reference electrode, with 1 M sodium sulfate solution as the electrolyte, the Tafel slope was measured. The results are as Figure 4 shown.

[0092] Figure 4 are the Tafel curves of the Ni-Co doped electrode obtained in Example 1 and the Ni-Fe-Co doped electrode obtained in Example 1.

[0093] Note: The values in [value] need to be filled with the actual current values in the original text.Among them, the calculation method of the Tafel curve slope is as follows:

[0094] η = a + b·log|j|

[0095] In the formula, η is the overpotential, j is the current density, a is the intercept, and b is the Tafel slope.

[0096] The Tafel slope is used to evaluate the catalytic activity and stability of the electrode. It can be seen from Figure 4 that the Tafel slope of the Ni-Co-Fe doped electrode is fitted to be 521 mV / dec, and the Tafel slope of the Ni-Co electrode is fitted to be 365 mV / dec, which proves that the catalytic activity of the synthesized Ni-Co-Fe electrode is significantly improved. In addition, it can be observed that the Tafel slope of the Ni-Co-Fe doped electrode remains stable during the electrochemical test and does not change significantly, indicating that the Ni-Co-Fe doped electrode obtained in the present invention has high catalytic stability.

[0097] 2. Test on the adsorption and removal effect of uranium in the uranium-containing solution:

[0098] Using the nickel foam electrode obtained in Example 1, the anodized nickel foam electrode obtained in Example 1, the Ni-Co doped electrode obtained in Example 1, and the Ni-Fe-Co doped electrode obtained in Example 1 as the working electrodes, a platinum electrode (with a cross-sectional size of 2 cm × 2 cm) as the counter electrode, and an Ag / AgCl electrode as the reference electrode, an aqueous solution with an initial uranium concentration of 50 ppm was used as the electrolyte, and a uranium removal experiment was carried out within 0 - 70 min. The results are as Figure 5 shown.

[0099] Figure 5 are the adsorption and removal effects of uranium by the nickel foam electrode obtained in Example 1, the anodized nickel foam electrode obtained in Example 1, the Ni-Co doped electrode obtained in Example 1, and the Ni-Fe-Co doped electrode obtained in Example 1.

[0100] It can be seen from Figure 5 that the Ni-Fe-Co doped electrode obtained in Example 1 can significantly improve the uranium extraction efficiency, and can achieve the removal of 100% of uranium within 30 min under the condition that the initial uranium concentration is 50 mg / L.

[0101] Using the Ni-Fe-Co doped electrode obtained in Example 1 as the working electrode, a platinum electrode (with a cross-sectional size of 2 cm × 2 cm) as the counter electrode, and an Ag / AgCl electrode as the reference electrode, aqueous solutions with initial uranium concentrations of 20 ppm, 50 ppm, 100 ppm, and 200 ppm were used as electrolytes, and a uranium removal experiment was carried out within 0 - 70 min. The results are as Figure 6 shown.

[0102] Figure 6 The uranium adsorption and removal effect of the Ni-Fe-Co doped electrode obtained in Example 1 on solutions containing different concentrations of uranium.

[0103] As Figure 6 can be seen, the Ni-Fe-Co doped electrode obtained in Example 1 can achieve the removal of more than 95% of uranium within 10 min under the condition that the initial uranium concentration is 20 mg / L.

[0104] In addition, in order to verify the uranium removal pathway of the Ni-Fe-Co doped electrode, the surface morphology of the Ni-Fe-Co doped electrode obtained in Example 1 after being treated for 70 min under the condition that the initial uranium concentration is 50 mg / L was also characterized, and the results are as Figure 7 shown.

[0105] Figure 7 It is the surface morphology diagram of the Ni-Fe-Co doped electrode obtained in Example 1 after the test of the uranium adsorption and removal effect on the uranium-containing solution.

[0106] As Figure 7 can be seen, after the extraction of uranium, the pores on the surface of the Ni-Fe-Co doped electrode obtained in Example 1 become fewer and the pore size becomes smaller, and obvious solid substances are deposited, proving that uranium exists on the electrode surface in the form of deposits, indicating that its uranium removal pathway is adsorption removal.

[0107] The Ni-Fe-Co doped electrode obtained in Example 1 after being treated for 70 min under the condition that the initial uranium concentration is 50 mg / L was also subjected to X-ray photoelectron spectroscopy analysis, and the results are as Figure 8 shown.

[0108] Figure 8 It is the X-ray photoelectron spectroscopy diagram of the Ni-Fe-Co doped electrode obtained in Example 1 after the test of the uranium adsorption and removal effect on the uranium-containing solution.

[0109] As Figure 8 can be seen, after the Ni-Co doped electrode obtained in Example 1 and the Ni-Fe-Co doped electrode obtained in Example 1 adsorb and remove uranium from the uranium-containing solution, uranium mainly exists in the hexavalent form (U(VI)) on the electrode, and at the same time, insoluble tetravalent uranium (U(IV)) also exists. The recovery of uranium can be achieved by the recovery of U(IV).

[0110] In this specification, each embodiment is described in a progressive manner. The key point of each embodiment is to illustrate the differences from other embodiments. For the same and similar parts among the embodiments, reference can be made to each other.

[0111] The foregoing description of the disclosed embodiments enables those skilled in the art to implement or use the present invention. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Thus, the present invention is not intended to be limited to the embodiments shown herein but is to be accorded the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A preparation method of a Ni-Co-Fe doped electrode for rapid uranium removal, characterized in that, It includes the following steps: Using a three-electrode system, with nickel foam as the working electrode, first perform anodic oxidation on it, then carry out cobalt deposition in an electrolyte containing a cobalt source, and finally carry out iron deposition in an electrolyte containing an iron source to obtain the Ni-Co-Fe doped electrode.

2. The preparation method according to claim 1, wherein, The reagent used for the anodic oxidation is a potassium hydroxide solution; the concentration of the potassium hydroxide solution is 2 - 4 M.

3. The preparation method according to claim 1, characterized in that, The voltage of the anodic oxidation is 2 - 3 V, and the time is 20 - 30 min.

4. The preparation method according to claim 1, characterized in that, When carrying out cobalt deposition, the electrolyte consists of boric acid, ammonium chloride, and a cobalt source; in the electrolyte during cobalt deposition, the concentration of boric acid is 0.5 - 1 M, the concentration of ammonium chloride is 1 - 3 M, and the concentration of the cobalt source is 0.1 - 0.5 M; the cobalt source includes one or more of cobalt nitrate, cobalt sulfate, and cobalt chloride.

5. The preparation method according to claim 1, wherein The current density of the cobalt deposition is 20 - 40 mA / cm 2 , and the time is 15 - 20 min.

6. The preparation method according to claim 1, wherein When carrying out iron deposition, the electrolyte consists of boric acid, ammonium chloride, and an iron source; in the electrolyte during iron deposition, the concentration of boric acid is 0.5 - 1 M, the concentration of ammonium chloride is 1 - 3 M, and the concentration of the iron source is 0.1 - 0.5 M; the iron source includes ferrous chloride and / or ferrous sulfate.

7. The preparation method according to claim 1, wherein, The current density of the iron deposition is 20-40 mA / cm 2 , and the time is 15-20 min.

8. The preparation method according to claim 1, characterized in that, Before the anodic oxidation, it also includes the step of cleaning the working electrode.

9. The Ni-Co-Fe doped electrode prepared by the preparation method according to any one of claims 1 - 8.

10. The application of the Ni-Co-Fe doped electrode according to claim 9 in the field of uranium removal.

Citation Information

Patent Citations

  • Iron-cobalt-nickel nano material, water electrolysis hydrogen production device and preparation method and application of iron-cobalt-nickel nano material

    CN115976592A

  • High-entropy Ni-Co-Fe-N-M hydroxide composite material as well as preparation and application thereof in electro-catalysis

    CN117230458A

  • Preparation method and application of Fe and Ni bi-metal co-doped coordinated regulation Co (OH) 2 catalyst

    CN118341428A

  • Thermal shock induced ferrocobalt double-doped metastable-phase nickel / nickel oxide heterostructure composite electrode as well as preparation method and application of thermal shock induced ferrocobalt double-doped metastable-phase nickel / nickel oxide heterostructure composite electrode

    CN119411158A

  • Electrolyte and the method of depositing metal layers especially of iron, cobalt, nikel, copper and zinc

    EP2045365A1